Internationalization, Technological Change and the Theory of the Firm - De Liso, Nicola; Leoncini, Riccardo (Studies in global competition, 2011)
This book focuses on three main areas, each of which is central to economic theorising: firms’ organisation and behaviour, technological change and the process of globalisation. Each subject can be analysed by using different methods, which range from purely theoretical abstractions to case studies and from econometrics to simulations. What this collection provides is a broad view of the three topics by concentrating on different aspects of each of them, and utilising different methods of investigation. Internationalization, Technological Change and the Theory of the Firm looks in detail at various questions surrounding firms’ organisation, including why we can observe ordered paths of production, whether proximity between firms matters, and whether patenting is always worthwhile. In addition, several essays explore technology and innovation, including the persistence-cum-development of old technologies. Furthermore, this book focuses on those processes which concern small- and medium-sized firms, considering the usefulness of stage theory, the possibilities of production off-shoring and the skill composition of manufacturing firms. Overall, the book is characterised by original ideas, renewed applications of mathematical and statistical methods and the use of new databases. This valuable collection will be of interest to postgraduates and researchers focusing on innovation, theories of the firm and globalisation; and should also be useful to a professional readership as it presents up-to-date research with the aim of improving our understanding of the phenomena of technological change, firms’ strategies, and globalisation. Introduction Nicola De Liso and Riccardo Leoncini Part I: Technological change, firms' organisation and incentives 1. The production process as a complex, dynamic and ordered world Mauro Lombardi 2. Incumbents’ strategies for platform competition: Shaping the boundaries of creative destruction Stefano Brusoni and Roberto Fontana 3. Linking technological change to organizational dynamics: Some insights from a pseudo-NK model Tommaso Ciarli, Riccardo Leoncini, Sandro Montresor and Marco Valente 4. Technological persistence through R&D on an old technology: The sailing-ship effect Nicola De Liso and Giovanni Filatrella 5. Software patents and firm's strategic behaviour in the EU: Some empirical insights Francesco Rentocchini and Giuditta De Prato Part II: Fragmentation and internationalisation of firms and of local systems of production 6. Does spatial proximity matter? Micro-evidence from Italy Giulio Cainelli and Claudio Lupi 7. Internationalization in Italian medium sized firms: Does stage theory explain the observed patterns? Donato Iacobucci and Francesca Spigarelli 8. Production offshoring and the skill composition of Italian manufacturing firms: A counterfactual analysis Roberto Antonietti and Davide Antonioli 9. A global network and its local ties: Competition and restructuring of the Benetton Group Paolo Crestanello and Giuseppe Tattara Nicola De Liso is Professor of Economics at the Faculty of Law of the University of Salento, Italy. Riccardo Leoncini is Professor of Economics at the Faculty of Law of the University of Bologna, Italy.